CISM Certified Information Security Manager practice exams - Gregory, Peter H. (ITpro collection, 2023)
Up-to-date practice questions that cover every topic on the 2022 version of the CISM exam Take the current version of the challenging CISM exam with complete confidence using the detailed information contained in this fully updated self-study guide. Written by an expert in the field, the book features hundreds of practice exam questions that match those on the live test in content, format, tone, and feel. In-depth answer explanations are provided for both the correct and incorrect answer choices. CISM Certified Information Security Manager Practice Exams, Second Edition supplements the CISM All-in-One Exam Guide and completely covers every objective of the 2022 exam release. In total, the book contains more than 300 realistic practice questions." Offers 100% coverage of all four CISM exam domains " Online content includes access to an additional 150 practice questions in the TotalTester Online customizable test engine " ritten by a computer security expert, author, and lecturer